Review of the genus Fibuloides Kuznetsov in China (Lepidoptera, Tortricidae, Olethreutinae) - Zhang, Aihuan (Pensoft Publishers, 2011)
Abstract. Species of the genus Fibuloides Kuznetsov that occur in China are reviewed. Fibuloides trapezoidea, sp. n.is described as new; Fibuloides levatana (Kuznetsov) and Fibuloides modificana Kuznetsov are newly recorded for China; Acroclita nigrovenana Kuznetsov, syn. n. is considered as a synonym of Fibuloides corinthia (Meyrick); and Eucoenogenes elongata Zhang & Li and Eucoenogenes wuyiensis Zhang & Li are transferred to Fibuloides, resulting in two new combinations. A key to the nine Chinese species of Fibuloides is given.